Editorial: The Digital Economy and Cyber Security - Campbell, Leith H. (Journal of Telecommunications and the Digital Economy, 2022)
This editorial comes in three parts: some remarks on developing a cyber security architecture for the digital economy; a note on changes to the Journal’s editorial team; and a brief introduction to the papers in this issue.